Design, Synthesis and Biological Screening of Novel Carbazole Tethered Oxyethylamino Derivatives as Antimicrobial Agent - Sabale, Prafulla M; Sayyad, Nusrat B; Potey, Lata C (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Carbazole is an important scaffold known to be associated with several biological activities including antimicrobial activities. Incorporation 4-oxothiazolidine moiety in carbazole moiety may lead to a new series of antimicrobials compounds. Aim: In this study, design and synthesis of novel carbazole tethered oxyethylamino was started with carbazole as basic pharmacophore and evaluated for antimicrobial activity. Materials and Methods: Molecular docking of carbazole derivatives was carried out by Schrödinger (Maestro 10.5v) active compound were Synthesized and screened for in vitro antimicrobial activity against Candida albicans and gram-positive and gram-negative bacterial strains such as Staphylococcus aureus, Bacillus subtilis, E. coli. MIC was calculated by standard agar tube dilution method. Results: All Compounds shown good antimicrobial activity at 25 (µg/ml) – 510 (µg/ml). The molecular docking studies demonstrated ligand protein interaction. Conclusion: carbazole represent novel set of lead for the designing of novel antimicrobial agents.
Keywords: Molecular Docking; Carbazole; Oxyethylamino; Antimicrobial activity; Antifungal activity